2015
DOI: 10.1155/2015/953045
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Ovarian Follicle Growth in Iran Viper (Vipera albicornuta)

Abstract: The Vipera albicornuta is an economically important snake of Iran, its venom is used for antivenin production, and we need to breed the snake in the captivity. In order to know about the viper's reproductive biology, seasonal alterations in ovarian weight, morphology, and the follicles developmental stages in Vipera albicornuta were studied using macroscopic parameters and histological examination of reproductive tissues during a year. Twenty-four female vipers were collected from mountainous zone of Bostanaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The relationship between body condition and reproductive activity is wellestablished in snakes; however, little is known about the thyroid hormonal regulating this relationship in snakes. At the present study, body weight of female Caucasian viper (C. viper) in summer was more than autumn and winter (P≤ 0.05) that may be because of snake activity in suitable temperature [37] and food availability [34] in summer that is similar to body fat increment in viviparous vipers according to Afsharzadeh, et al [38], following mating, the body weight of snake have decreased in autumn. Our previous studies have shown male C. vipers have summer/ aestival spermatogenesis [37] and mating with female may occur at the time of ovulation in summer [39,40].…”
Section: Discussionsupporting
confidence: 48%
“…The relationship between body condition and reproductive activity is wellestablished in snakes; however, little is known about the thyroid hormonal regulating this relationship in snakes. At the present study, body weight of female Caucasian viper (C. viper) in summer was more than autumn and winter (P≤ 0.05) that may be because of snake activity in suitable temperature [37] and food availability [34] in summer that is similar to body fat increment in viviparous vipers according to Afsharzadeh, et al [38], following mating, the body weight of snake have decreased in autumn. Our previous studies have shown male C. vipers have summer/ aestival spermatogenesis [37] and mating with female may occur at the time of ovulation in summer [39,40].…”
Section: Discussionsupporting
confidence: 48%
“…The timing of the different stages of the reproductive cycle of males of the present study could generally be compared with that for other snake species of the Middle East such as the grass snake, Natrix natrix (Faghiri et al, 2011) and the dice snake, Natrix tessellata (Savasari et al, 2015) in northern Iran. The reproductive cycle of females could also be compared with that of other serpents of the region such as the Iran viper, Vipera albicornuta (Afsharzadeh et al, 2015). Synchronization between the reproductive activities of both males and females of the Schokari sand racer, Psammophis schokari, in Israel was recorded in spring (Goldberg, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The male reproductive cycle of P. florulentus could thus be referred to as a vernal cycle (Savasari et al, 2015). Ovulation in females of this species follows the peak of spermatogenesis in males so that, the female reproductive cycle could be referred to as a prenuptial cycle (Afsharzadeh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%